Advances in Markov-Switching Models 2002
DOI: 10.1007/978-3-642-51182-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Improving GARCH volatility forecasts with regime-switching GARCH

Abstract: Many researchers use GARCH models to generate volatility forecasts. Using data on three major U.S. dollar exchange rates we show that such forecasts are too high in volatile periods. We argue that this is due to the high persistence of shocks in GARCH forecasts. To obtain more flexibility regarding volatility persistence, this paper generalizes the GARCH model by distinguishing two regimes with different volatility levels; GARCH effects are allowed within each regime. The resulting Markov regime-switching GARC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 31 publications
1
78
0
6
Order By: Relevance
“…The interesting feature of these models lies in the fact that they provide an explanation of the high persistence in volatility, i.e., nearly unit root process for the conditional variance, observed with single-regime GARCH models (Lamoureux and Lastrapes 1990). Furthermore, these models are apt to react quickly to changes in the volatility level (unconditional volatility) which leads to significant improvements in volatility forecasts as shown by Dueker (1997) or Klaassen (2002) for instance. These features make the models attractive for various applications in financial modeling, such as risk management.…”
Section: Application Ii: Log-returns Of the Swiss Market Indexmentioning
confidence: 99%
“…The interesting feature of these models lies in the fact that they provide an explanation of the high persistence in volatility, i.e., nearly unit root process for the conditional variance, observed with single-regime GARCH models (Lamoureux and Lastrapes 1990). Furthermore, these models are apt to react quickly to changes in the volatility level (unconditional volatility) which leads to significant improvements in volatility forecasts as shown by Dueker (1997) or Klaassen (2002) for instance. These features make the models attractive for various applications in financial modeling, such as risk management.…”
Section: Application Ii: Log-returns Of the Swiss Market Indexmentioning
confidence: 99%
“…More details can be found in Klaassen (2002). The advantage of this approach is that it allows to calculate the log likelihood function and multi-step ahead volatility forecasts recursively as in standard GARCH models.…”
Section: Description Of Mrs-garch Modelmentioning
confidence: 99%
“…Finally, we focused on 2 symmetric distributions, namely the Student-t and Normal distributions. The Student-t distribution has the advantage of being more heavy-tailed than the Normal distribution, making the regimes more stable [25]. Its drawback is that it has one extra parameter (its degree of freedom) which is difficult to estimate [26].…”
Section: Wind Power Predictive Densitymentioning
confidence: 99%
“…Regarding maximum likelihood methods, the idea consists in approximating the conditional variance as a sum of past conditional variance expectations as in [26]. This model was later extended by [25] yielding improved volatility forecasts. Alternatively, Haas et al [35] suggested a new formulation for MS-GARCH models by disaggregating the overall variance process into separate processes in each regime.…”
Section: Existing Markov Switching Models With Garch Errorsmentioning
confidence: 99%
See 1 more Smart Citation